Trinitarian perspectives in the Franciscan theological tradition - Calisi, Maria (St. Bonaventure, NY : Franciscan Institute, St. Bonaventure University, 2008)
Trinitarian Perspectives in the Franciscan Theological Tradition by Dr. Maria Calisi builds substantially on the previous volumes in the Franciscan Heritage series sponsored by the Secretariat for the Retrieval of the Franciscan Intellectual Tradition (CFIT) of the English Speaking Conference of the Order of Friars Minor. Dr. Calisi is an authority on the theology of Saint Bonaventure. Her exposition of the foundations of the Seraphic Doctor's theology in the contemplative experience of and reflection on the relational nature of God's life retrieves an important theological perspective applicable to our contemporary search for meaning. Well schooled in the patristic inheritance, Calisis engages the reader with a simple but profound analysis of the creedal sign shared by all Christians: In the name of the Father, Son and the Holy Spirit. In these pages we will discover how doctrine can shape life, and life, doctrine; how faith-filled human beings rooted in Trinitarian love can bear great fruit for both Church and society by engaging practitioners in action supportive of personal dignity, ecumenical relationships, social transformation, and ecclesial reform.
The scriptural revelation and trinitarian theology -- Bonaventure's trinitarian theology -- Bonaventure, Francis, and the experience of the tri-personal God.
Includes bibliographical references (pages 89-91).
Print version record.
Keywords: Trinity; Francis, -- of Assisi, Saint, -- 1182-1226.; Bonaventure, -- Saint, Cardinal, -- approximately 1217-1274.; Franciscans -- Theology; Bonaventure -- Saint, Cardinal -- approximately 1217-1274 -- Criticism and interpretation; Franciscans -- Theology; Trinity -- History of doctrines -- Catholic authors; RELIGION -- Christian Theology -- General; RELIGION -- Christian Theology -- Christology; Bonaventure, -- Saint, Cardinal, -- approximately 1217-1274.; Francis, -- of Assisi, Saint, -- 1182-1226.; Franciscans; Theology; Trinity; Electronic books